POETIC STEREOTYPES IN AND OF IMAGES OF SLOVAKIA IN THE CZECH POETRY OF 1860-1939 - Tureček, Dalibor (Porównania, 2019)
A study devoted to the image of Slovakia in the Czech poetry of 1860-1939, ie poetic stereotypes, which were formed even before the creation of a common Czech-Slovak state in 1918. Slovakia was then perceived in a romantic spirit as a beautiful land with virgin nature and people not affected by the corruption of civilization. The aspirations of the Slovaks to language and national self-determination were negatively assessed – not considering the historical, ethnic and political aspects, Slovakia became a natural part of the Czech national project. The reference of Czechs to Slovaks with a sense of superiority, their attitude of “elder brother” can be defined, somewhat hyperbolically, as a colonial one.